2014
DOI: 10.2166/wst.2014.199
|View full text |Cite
|
Sign up to set email alerts
|

New equation for the computation of flow velocity in partially filled pipes arranged in parallel

Abstract: This paper presents a new approach for the computation of flow velocity in pipes arranged in parallel based on an analytic development. The estimation of the flow parameters using existing methods requires trial and error procedures. The assessment of flow velocity is of great importance in flow measurement methods and in the design of drainage networks, among others. In drainage network design, the flow is mostly of free surface type. A new method is developed to eliminate the need for trial methods, where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several researchers tried to propose an exact solution of the Colebrook-White equation (which is relevant only for turbulent flow [1,7])with the hope of achieving zero-percent (0%) maximum deviation as proposed in similar research [8][9][10], however simple formulas are always be preferred for highly computationally efficient [1,3]. The authors have presented an interesting work where the Right ω-function and the Padé approximation were used.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers tried to propose an exact solution of the Colebrook-White equation (which is relevant only for turbulent flow [1,7])with the hope of achieving zero-percent (0%) maximum deviation as proposed in similar research [8][9][10], however simple formulas are always be preferred for highly computationally efficient [1,3]. The authors have presented an interesting work where the Right ω-function and the Padé approximation were used.…”
Section: Resultsmentioning
confidence: 99%
“…Sewersheds may be arranged in series (Zeghadnia et al 2014b) or in parallel. In this study, the authors focus on the second case, where the pipes are arranged in parallel as shown in Fig.…”
Section: Analytical Formulationmentioning
confidence: 99%